(untitled) (Journal of Dhaka Medical College, 2011)
Vesicouterine fistula is a very rare urogenital fistula but may be iatrogenic, following a Caesarean section operation. Presentation and position of fistulas make their diagnoses very difficult. Hysteroscopy, cystoscopy, hysterosalphingography, Computed Tomography scan and Magnetic Resonance Imaging are very useful to diagnose the condition precisely. History of the patient, clinical examination and instillation of methylene blue into the uterine cavity through cervix or through the urethra are an option to diagnose vesicouterine fistula in a low resource centre. Key words: Vesicouterine fistula; Menouria; Caesarean section. DOI: 10.3329/jdmc.v19i2.7088 J Dhaka Med Coll. 2010; 19(2) : 150-153